2016
DOI: 10.1039/c6ra17137k
|View full text |Cite
|
Sign up to set email alerts
|

A novel highly dispersive magnetic nanocatalyst in water : glucose as an efficient and green ligand for the immobilization of copper(ii) for the cycloaddition of alkynes to azides

Abstract: A new heterogeneous and highly dispersive nanocatalyst in water was prepared by the immobilization of Cu2+ onto glucose on Fe3O4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In previous study, we tried to stabilize Cu 2+ onto the Fe 3 O 4 which was functionalized with glucose, in order to synthesize different derivatives of 1,2,3‐triazole via one‐pot three‐component reaction of alkynes, alkyl halides, and sodium azide. In this study, we made an effort to immobilize Pd 2+ onto the magnetic nanoparticles of Fe 3 O 4 –silica coated and usage of this nanocatalyst in the synthesis of benzoxazole derivatives with 2‐aminophenol and an aromatic aldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…In previous study, we tried to stabilize Cu 2+ onto the Fe 3 O 4 which was functionalized with glucose, in order to synthesize different derivatives of 1,2,3‐triazole via one‐pot three‐component reaction of alkynes, alkyl halides, and sodium azide. In this study, we made an effort to immobilize Pd 2+ onto the magnetic nanoparticles of Fe 3 O 4 –silica coated and usage of this nanocatalyst in the synthesis of benzoxazole derivatives with 2‐aminophenol and an aromatic aldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic nanoparticle (Fe 3 O 4 ) was synthesized using the co-precipitation approach 101 , 102 . After synthesizing it, Fe 3 O 4 @SiO 2 (1 g) was dispersed in dry EtOH and NH 4 OH (2 mL) was added to the mixture.…”
Section: Methodsmentioning
confidence: 99%
“…In a related approach, many investigations explored the coating of nano-ferrites with a functionalized shell to reduce the aggregation of the nanoparticles in the solution and improve the catalyst's efficiency by increasing the number of functional groups on the surface. Among these, Moghaddam et al [132] reported the immobilization of glucose (GLU) onto MNPs of Fe 3 O 4 -silica to stabilize copper(II), and studied their catalytic activity under greener conditions for the one-pot [3+2] cycloaddition reaction of alkyl halides, sodium azide, and alkynes using water as solvent (Figure 11). The use of 5 mol% of (MNPs@GLU)Cl ( 33) catalyst produced excellent yields (76-99% in 1-8 h) in the synthesis of various 1,4-triazole derivatives at 50 • C, due to the high dispersity of the catalyst in water by creating hydrogen bonds with the glucose.…”
Section: Magnetic Solid-supported Catalysts For Cuaacmentioning
confidence: 99%